2019
DOI: 10.3390/jcdd6030026
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerable Plaque, Characteristics, Detection, and Potential Therapies

Abstract: Plaque development and rupture are hallmarks of atherosclerotic vascular disease. Despite current therapeutic developments, there is an unmet necessity in the prevention of atherosclerotic vascular disease. It remains a challenge to determine at an early stage if atherosclerotic plaque will become unstable and vulnerable. The arrival of molecular imaging is receiving more attention, considering it allows for a better understanding of the biology of human plaque and vulnerabilities. Various plaque therapies wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 200 publications
(264 reference statements)
1
53
0
2
Order By: Relevance
“…This was clearly shown by increased necrotic core area and regression of fibrous and fibrofatty areas. [13][14][15] These findings are supported by previous studies that showed high WSS as a contributor to plaque rupture in coronary and carotid arteries. [36][37][38][39] Similarly, a randomized clinical trial with 3 years follow-up showed that high WSS could predict myocardial infarction in stable CAD.…”
Section: Discussionsupporting
confidence: 86%
“…This was clearly shown by increased necrotic core area and regression of fibrous and fibrofatty areas. [13][14][15] These findings are supported by previous studies that showed high WSS as a contributor to plaque rupture in coronary and carotid arteries. [36][37][38][39] Similarly, a randomized clinical trial with 3 years follow-up showed that high WSS could predict myocardial infarction in stable CAD.…”
Section: Discussionsupporting
confidence: 86%
“…An elevated low-density lipoprotein (LDL) levels are an important predictor in the diagnosis of atherosclerosis. 2 The oxidation of LDL is the primary event that takes place in atherosclerosis. Studies have found that serum uric acid (UA) levels are directly proportional to the levels of triglycerides (TG), total cholesterol (TC), and LDLs.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of atherosclerosis occurs regardless of sex and ethnicity. An elevated low‐density lipoprotein (LDL) levels are an important predictor in the diagnosis of atherosclerosis 2 . The oxidation of LDL is the primary event that takes place in atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Third, correlation coefficients are effect sizes, so in real terms, we do not need a p-value to interpret them. Finally, currently various techniques and biomarkers (e.g., biochemical, genetic, imaging) have been proposed to assess the characteristics of atherosclerotic plaques (e.g., to identify vulnerable plaques) [47]. Among imaging biomarkers for vulnerable plaques, echography/virtual histology, computed tomography, spectroscopy, optical coherence tomography, high-frequency intravascular ultrasound and magnetic resonance imaging were described [47].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Finally, currently various techniques and biomarkers (e.g., biochemical, genetic, imaging) have been proposed to assess the characteristics of atherosclerotic plaques (e.g., to identify vulnerable plaques) [47]. Among imaging biomarkers for vulnerable plaques, echography/virtual histology, computed tomography, spectroscopy, optical coherence tomography, high-frequency intravascular ultrasound and magnetic resonance imaging were described [47]. In our work we opted for using B-Mode echography/virtual histology, since (a) we worked with peripheral plaques (non-coronary), and (b) we proposed to consider selecting a non-invasive and innocuous technique widely used in clinical practice [27,28].…”
Section: Strengths and Limitationsmentioning
confidence: 99%